Relative bioenergy potentials of major agricultural crop residues in the Philippines - Mendoza, T. C.; Samson, R. (2006)
Four major agricultural by-products (sugarcane bagasse and trash, rice hulls, coconut, and maize cobs) of the Philippines are assessed in terms of their bioenergy potentials, their ease of recovery and retrieval from the field to the site of utilization, and their relative importance in the farm landscape. About 4.5 M tonnes of coconut fronds, 1.5 M tonnes of rice hull, 1.17 M tonnes of sugarcane trash and 0.5 M tonnes of corn cobs are estimated to be recoverable. Sugarcane trash residues are better left in the field to increase soil organic matter, reduce fertilizer requirements of sugarcane and increase sugar yields. But in the final year of the ratoon crop, harvesting trash for bioenergy appears economical. Under this scheme, the recoverable trash residue is 391,000 tonnes. About 640,000 tonnes of surplus bagasse (50%moisture) is available from mills that produce raw sugar, but sugar mills with refineries or distillery operations consume the excess bagasse. Thus, in reality, there is no surplus of bagasse. Soil erosion, depletion of the nutrient pool, and loss of soil organic matter are known to occur when the aboveground portions of the plants harvested are taken away. however, the maize cob is a viable fraction that can be collected. It is widely utilized by small farmers for cooking. Rice straw is abundant in the field but it is high in silica content, has low energy potential, and is high in retrieval costs. This makes it as inferior resource for major bioenergy development. As in sugarcane trash and maize stalls, rice straw is best left in the field to decompose to maintain soil organic matters levels and to enhance N₂faxation during the decomposition process. Mostly, rice hulls are currently being burned, but they can be effectively utilized as bioenergy resource. The two main advantages of using rice hulls are that they have widespread availability and require no prior processing before burning. They are well suited to low grade heating applications such as household cooking or crop drying. The 300M coconut trees in the Philippines annually produce tremendous amounts of biomass as husk (4.1 M tonnes), shell (1.8 M tonnes), and frond (4.5 M tonnes). The recovery of these residues is labor-intensive, and much more of these materials are available in remote areas. coconut fronds are good resource for household cooking. As fossil fuel prices continue to rise, rice hulls and coconut fronds are the two most important but underdeveloped biomass resources that could be fully utilized as bioenergy in a relatively short time period. There is comparative advantage in converting marginal soils planted to grain maize into perennial biomass energy plots using Napier grass (Pennisetum purpureum).
Keywords: Crop residues; Biomass energy